Napływ kapitału zagranicznego do Polski w procesie integracji i globalizacji - Kociszewski, Jerzy; Popławski, Maciej (Inflow of Foreign Capital to Poland in the Process of Integration and Globalization, 2005)
In the scientific there is done the analysis of the foreign direct investments (FDI) in the world's economy according to the phases, elements actuating the FDI inflow, structure according to the investors' origin, kinds and forms. There is analysis of the FDI in Poland in the system transformation period, in particular of the reasons, stages, elements, forms and direct and indirect effects of the foreign capital inflow to Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 160-170